Why potential donors do not become actual donors: an exploratory-descriptive study - Mouro, Selma Delgado de Souza; Guillens, Luiz Carlos; Almeida, Thamara Chagas de; Duran, Erika Christiane Marocco; Toledo, Vanessa Pellegrino (Revista de Enfermagem UFPE on line, 2012)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> ABSTRACT Objectiove: to characterize potential donors from brain death (BD) notifications according to age and gender, as well as to identify the notifications, quantify and quality the main causes of BD, to check actual donations, survey the causes of non-donation of organs and identify the causes why potential donors (PD) do not become actual donors in the region of Campinas, São Paulo State, Brazil, between January and December 2009. Method: descriptive, exploratory and retrospective research; 294 PD files that went through the donation process were studied. Approval was obtained from the Institutional Review Board at Fundação Hermínio Ometto, opinion No 234/2010. Results: based on analysis, it was identified that 53.06% of PD were male and that the most frequent age range was between 35 and 49 years old (32.31%). Causes of BD included cerebrovascular accident and death by trauma; causes of non-effectuation were cardiac arrest, medical counter-indication, non-authorization by the family and positive serology; the cities with the highest PD rate were Campinas (31.63%), followed by Jundiaí and São José dos Campos (9.86%). Conclusion: the high organ capitation rate is possible due to donor identification and the implementation of computerized pre-registered donor systems, besides different interventions health professionals, administrators and ethics experts put in practice, including the offering of financial incentives for organ donation, the legalization of presumed consent, among others. Descriptors: donations; directed tissue donation; brain death. RESUMO Objetivo: caracterizar os potenciais doadores das notificações de morte encefálica(ME) de acordo com a idade e o sexo. Metodologia: estudo de caráter quantitativo, descritivo, exploratório e retrospectivo, com 294 prontuários de potenciais doadores de janeiro a dezembro de 2009, notificados à Organização de Procura de Órgãos, do Hospital de Clínicas, da Universidade Estadual de Campinas, após a aprovação pelo Comitê de Ética e Mérito em Pesquisa sob o parecer n°234/2010. A descrição dos dados foi pela análise da frequência absoluta e relativa. Resultados: 53,06% do Potencial Doador eram do sexo masculino, faixa etária entre 35 a 49 anos de idade (32,31%); dentre as causas de morte encefálica figuraram acidente vascular encefálico e mortes por traumas; as causas da não-efetivação foram parada cardíaca, contra-indicação médica, não autorização familiar e sorologia positiva; os municípios que tiveram maior índice de Potencial Doador foram Campinas (31,63%), seguida por Jundiaí e São José dos Campos (9,86%). Conclusão: estudos demonstram que a alta taxa de captação de órgãos é possível devido à identificação de doadores e de implementação de sistemas informatizados de pré-cadastros, além de diversas intervenções implementadas por profissionais de saúde, administradores e especialistas em ética, que incluem oferecimento de incentivos financeiros para a doação de órgãos, a legalização de consentimento presumido, a colheita de rotina e a introdução de uma resposta necessária a um pedido legalmente estipulado. Descritores: doações; doação dirigida de tecido; morte encefálica. RESUMEN Objetivo: caracterizar los potenciales donadores de las notificaciones de muerte encefálica (ME) según la edad y el sexo, y también identificar las notificaciones, cuantificar y cualificar las principales causas de la ME, verificar las donaciones efectuadas, recoger las causas de no-donación de órganos e identificar las causas de la no efectuación de potenciales donadores (PD) en donadores reales, en la región de Campinas, estado de São Paulo, Brasil, en el período de enero a diciembre del 2009. Metodología: estudio descriptivo, exploratorio y retrospectivo; 294 archivos de PD que pasaron por el proceso de donación fueron estudiados, siendo aprobado por el Comité de Ética e Investigación de la Fundação Hermínio Ometto bajo el parecer n°234/2010. Resultados: el análisis permitió la identificación del 53,06% de los PD del sexo masculino, rango de edad más frecuente entre 35 y 49 años de edad (32,31%). Se constató que las causas de ME incluyeron accidente vascular encefálico y muertes por traumas; las causas de la no-efectuación fueron parada cardíaca, contra-indicación médica, no autorización familiar y serología positiva; los municipios con mayor índice de PD fueron Campinas (31,63%), seguida por Jundiaí y São José dos Campos (9,86%). Conclusión: la alta tasa de captación de órganos es posible debido a la identificación de donadores y la implementación de sistemas informatizados de pre-registrados, además de diversas intervenciones implementadas por profesionales de salud, administradores y especialistas en ética, que incluyen el ofrecimiento de incentivos financieros para la donación de órganos, la legalización del consentimiento presumido, entre otros. Descriptores: donaciones; donación dirigida de tejido; muerte encefálica.